Studies on the Antibacterial activity of 3,5-Diaryl Pyrazolines and 3,5-Diaryl Pyrazoles - V.B. Tayde, Miss; Jamode, V.S. (Asian Journal of Chemistry, 2010)
Some new 3,5-diaryl pyrazolines and 3,5-diaryl pyrazoles havebeen synthesized by a novel method. Structures of these compoundshave already been characterised by spectral analysis. Listed compoundswere tested for their antibacterial activity and are found tohave remarkable activity.